Is social protection in Ghana a right?. Issue 8 (17th November 2019) - Abdulai, Abdul-Gafaru; Abubakari, Abdul-Bassit; Martey, Jude
ABSTRACT: Through an analysis of Ghana's Livelihood Empowerment Against Poverty (LEAP) programme, this article examines the extent to which national governments have embraced the rights-based approach to social assistance. Based on interviews with beneficiary households and policymakers at national and sub-national levels, it finds that although official policy documents depict the LEAP in rights-based terms, beneficiaries see it as a charitable programme. The article concludes that if the LEAP is to play a stronger role in promoting citizenship rights in Ghana, it is important to strengthen district level structures to investigate and redress beneficiaries' complaints in a timely manner.